Depiction of Social Class in ‘Pride and Prejudice and Zombies’ Novel - Sanjaya, Adjie Aditya (Research Community for Critical Society and Environment, 2025)
Literary texts frequently function as cultural artifacts that reflect and critique the socio-economic structures of their time. One such structure is the hierarchical division of society into distinct social classes, often determined by access to wealth, power, and privilege. This study explores the representation of class dynamics in Pride and Prejudice and Zombies by Jane Austen and Seth Grahame-Smith, with particular attention to the symbolic positioning of zombies with human characters. Utilizing a descriptive qualitative methodology and grounded in Karl Marx’s theory of class struggle within a sociological literary framework, the research examines how the novel constructs and reinforces social stratification. The study offers a distinctive contribution by interpreting the human-zombie dichotomy as a metaphor for entrenched class divisions, thereby extending Marxist analysis into the domain of genre fiction. The findings suggest that zombies are not merely monstrous figures but serve as symbolic representations of the oppressed lower class, subjected to marginalization and dehumanization by the elite. This narrative dynamic reflects broader concerns surrounding class-based prejudice and systemic inequality. Through its hybridization of horror and classic literature, the novel becomes a site for critical engagement with socio-economic hierarchies, illustrating how genre fiction can serve as a vehicle for ideological critique.